Castor oil for induction of labor in post-date pregnancies: A randomized controlled trial. Issue 1 (February 2018) - Gilad, Ronit; Hochner, Hagit; Savitsky, Bella; Porat, Shay; Hochner-Celnikier, Drorith
Abstract: Background: Castor oil is a substance used for labor induction in an inpatient setting. However, its efficacy as an agent for the induction of labor, for post-date pregnancies in an outpatient setup is unknown. Objective: Efficacy of castor oil as an agent for the induction of labor, for post-date pregnancies in outpatient settings. Methods: Eighty-one women with a low-risk post-date singleton pregnancy with a Bishop score ≤ 7, without effective uterine contractions were randomized to the intervention, 60 ml of castor oil, or the control, 60 ml of sun-flower oil. The primary outcome was proportion of women entering the active phase of labor 24, 36, 48 h after ingestion. Secondary outcomes included meconium stained amniotic fluid, abnormal fetal heart rate tracing, cesarean section rate, instrumental deliveries, birth weight, 5 min Apgar score, chorioamnionitis, hypertensive complications, retained placenta, and post-partum hemorrhage. Findings: Intervention and control groups included 38 and 43 women, respectively. No differences in baseline characteristics, except for age were noted. The observed interaction between castor oil and parity was significant (pinteraction = 0.02). Multiparous women in the intervention group exhibited a significant beneficial effect on entering active labor within 24, 36 and 48 h after castor oil consumption compared with the placebo (Hazard Ratio = 2.93, p = 0.048; Hazard Ratio = 3.29, p = 0.026; Hazard Ratio = 2.78, p = 0.042 respectively). This effect was not noted among primiparous women. No differences in rate of obstetric complications or adverse neonatal outcomes were noted. Conclusion: Castor oil is effective for labor induction, in post-date multiparous women in outpatient settings.